Integrating Bio-Hubs for Resilience Enhancement of Wood Pellet Supply Chains: A Market Analysis using System Dynamics - Mohagheghi, Omid; Mafakheri, Fereshteh; Nasiri, Fuzhan; Gagnon, Bruno; Prinz, Robert; Bergström, Dan; Brown, Mark (Elsevier, 2026)
Wood pellets have become a standardized commodity in the global energy market, with rapidly growing international trade. Canada, with its vast forest resources, has significant potential to expand its share of the global wood pellet market. However, the wood pellet industry faces multiple challenges on both the supply and demand sides of the supply chain. This study assesses the role of bio-hubs in enhancing the resilience and competitiveness of Canadian wood pellets in the global market. Bio-hubs are centralized facilities that aggregate, process, store, and redistribute bioenergy products, enabling improved logistics coordination, cost efficiency, and supply flexibility across the supply chain. Using a System Dynamics (SD) approach, the integration of bio-hubs into wood pellet supply chains (WPSCs) is modeled to evaluate their impacts on supply and demand dynamics under various scenarios. The model captures key complexities of WPSCs, including feedstock supply disruptions of 25% and 50%, macroeconomic demand-side changes in importing countries represented by GDP variations of ±20% and ±40%, and interactions with parallel energy markets through fossil fuel price changes of ±20% and ±40%. The results show that the inclusion of bio-hubs significantly strengthens supply chain resilience and enhances Canada's competitive position. The findings indicate that Canada has the potential to emerge as a leading global supplier, capturing approximately 50% of the global wood pellet market share. These results highlight bio-hubs as a critical strategic mechanism for supporting the long-term growth and stability of Canada's wood pellet industry despite market volatility and supply-side uncertainties.
Keywords: bio-hubs; wood pellet supply chains; wood pellet market; resiliency; system dynamics modeling; bioenergy